Dietary polyphenols as a safe and novel intervention for modulating pain associated with intervertebral disc degeneration in an in-vivo rat model - Lai, Alon; Ho, Lap; Evashwick-Rogler, Thomas W.; Watanabe, Hironobu; Salandra, Jonathan; Winkelstein, Beth A.; Laudier, Damien; Hecht, Andrew C.; Pasinetti, Giulio M.; Iatridis, James C. (PloS one, 2019)
Developing effective therapies for back pain associated with intervertebral disc (IVD) degeneration is a research priority since it is a major socioeconomic burden and current conservative and surgical treatments have limited success. Polyphenols are naturally occurring compounds in plant-derived foods and beverages, and evidence suggests dietary supplementation with select polyphenol preparations can modulate diverse neurological and painful disorders. This study tested whether supplementation with a select standardized Bioactive-Dietary-Polyphenol-Preparation (BDPP) may alleviate pain symptoms associated with IVD degeneration. Painful IVD degeneration was surgically induced in skeletally-mature rats by intradiscal saline injection into three consecutive lumbar IVDs. Injured rats were given normal or BDPP-supplemented drinking water. In-vivo hindpaw mechanical allodynia and IVD height were assessed weekly for 6 weeks following injury. Spinal column, dorsal-root-ganglion (DRG) and serum were collected at 1 and 6 weeks post-operative (post-op) for analyses of IVD-related mechanical and biological pathogenic processes. Dietary BDPP significantly alleviated the typical behavioral sensitivity associated with surgical procedures and IVD degeneration, but did not modulate IVD degeneration nor changes of pro-inflammatory cytokine levels in IVD. Gene expression analyses suggested BDPP might have an immunomodulatory effect in attenuating the expression of pro-inflammatory cytokines in DRGs. This study supports the idea that dietary supplementation with BDPP has potential to alleviate IVD degeneration-related pain, and further investigations are warranted to identify the mechanisms of action of dietary BDPP.